Beclometasone dipropionate/formoterol maintenance and reliever therapy asthma exacerbation benefit increases with blood eosinophil level. Issue 1 (8th July 2021) - Brusselle, Guy; Nicolini, Gabriele; Santoro, Luigi; Guastalla, Daniele; Papi, Alberto
A number of studies have evaluated the effectiveness of a "maintenance and reliever therapy" (MART) regimen combining in a single inhaler the rapid-acting, long-acting β2 -agonist (LABA) formoterol fumarate (FF) with an inhaled corticosteroid (ICS) in asthma [1–5]. Such a regimen is now established for the treatment of moderate-to-severe asthma in adolescents and adults in many guidelines [6, 7]. Furthermore, rescue short-acting β2 -agonists (SABAs) are no longer recommended as sole therapy even for patients with mild asthma, and an ICS/FF combination used as needed is the preferred reliever therapy [6]. BDP/FF MART regimen reduced the incidence of severe asthma exacerbations compared with BDP/FF maintenance therapy plus salbutamol as needed across the blood eosinophil continuum, with a trend to a greater reduction in patients with higher baseline counts https://bit.ly/3AGSMaX